The Role of Baitul Maal Wat Tamwil Financing and Business Coaching on Business Development and Welfare Improvement of Micro Traders in Traditional Markets - Emile Satia Darma; Syafira Firdaus Lisfebrianty Handoyo (Journal of Accounting and Investment, 2022)
Research aims: This study aims to analyze the role of financing and business coaching in BMT (Baitul Maal Wat Tamwil). The role of financing and business coaching focused more on its impact on business development and improved welfare of BMT members who carried out financing. BMT members here were specifically from micro-enterprises by traditional market traders.Design/Methodology/Approach: Market traders used as objects were still micro-scaled in traditional markets in Purworejo Regency, Central Java. In this study, the obtained data that could be processed were 72 respondents from 18 traditional markets. Then, the analysis tool used Structural Equation Modeling (SEM) – Variance Based. Research findings: The results of this study exhibited that business coaching had a significant positive effect on business development and welfare improvement of traditional market traders who were still on a micro-scale. The development of these businesses also affected the improvement of their welfare. However, BMT financing did not affect traditional market traders' business development and welfare improvement.Theoretical contribution/Originality: This study applied Community Development Theory and Constructive Perception Theory to BMT members' perceptions of business development and welfare improvement. The assessment of business development and welfare improvement was based on the respondents' perceptions, not on numerical standards that came from outside. It is hoped that in this way, the sustainability of the role of BMT towards its members will be more maintained and objective.Practitioner/Policy implication: An important implication of this study's results is that BMT's business coaching for its members, even with relatively small financing, will positively impact their perception of business development and welfare improvement. It can be used to create a better relationship between BMT and its members.Research limitation/Implication: The limitation of this study is that it only used the business coaching variable as a BMT coaching tool for its members. It is also possible that other variables can be used as a tool to maintain good relations between BMT and its members.